Public Beliefs About Somatic Symptom Disorders - von dem Knesebeck, Olaf; Löwe, Bernd; Lehmann, Marco; Makowski, Anna C. (Frontiers in Psychiatry, 2018)
Objectives: Despite satisfactory effectiveness of treatment for somatic symptom disorders (SSD), treatment rates are low and treatment is usually initiated many years after first symptoms. In order to understand whether a lack of public mental health literacy might contribute to these poor treatment rates, we aimed to focus on two research questions: 1) What does the German public know and think about SSD? 2) Are knowledge and beliefs associated with socio-demographic factors and experiences with the disorder? Methods: Two vignettes with symptoms of a SSD were used in a national telephone survey in Germany (N=1,004). Vignettes differed regarding main type of symptom (pain vs. fatigue) and existence of an earlier somatic disease (yes vs. no). Respondents were asked concerning knowledge and beliefs about causes, symptoms, and treatment using a standardized questionnaire. Results: 66% of the respondents agreed that a possible cause of the symptoms is a misinterpretation of body signals. About 1/3 recognized a mental health problem when confronted with the vignettes of cases with SSD. This rate was lower in case of a SSD with pain as the main symptom without a comorbid somatic disease (24.8%, 95%-CI: 21.1 - 28.6) compared to a case with fatigue as the main symptom and an earlier severe somatic disease (44.0%, 95%-CI: 39.6 - 48.3). Female respondents tended to have a more positive view on treatability and effectiveness of psychotherapy, while associations of knowledge and beliefs with education and age were inconsistent. Respondents who had contact with a person with SSD were more likely to think that psychotherapy is effective and that they know a lot about SSD compared to those who never had contact. Conclusions: While most of the German public seems to be well informed about causes of SSD as well as treatability and the effectiveness of psychotherapy, the majority has problems with interpreting symptoms and does not think they know a lot about symptoms like that. Increasing knowledge about SSD by education interventions may help to promote adequate help seeking.